2022
DOI: 10.34172/ijhpm.2022.6426
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of Regional Organisations in Strengthening Health Research Systems in Africa: Activities, Gaps, and Future Perspectives

Abstract: Background: Regional cooperation on health in Africa is not new. The institutional landscape of regional cooperation for health and health research, however, has seen important changes. Recent health emergencies have focussed regional bodies’ attention on supporting aspects of national health preparedness and response. The state of national health research systems is a key element of capacity to plan and respond to health needs – raising questions about the roles African regional bodies can or should play in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 36 publications
2
11
0
Order By: Relevance
“…International organisations, like the WHO Regional Office for Africa (WHO AFRO), have well-documented involvement and influence on African health research agendas and capacity as evidenced by the ongoing studies by WHO AFRO using data from the African Barometer collected from health research focal points in country [32] or similar studies with the WHO Regional Office for the Eastern Mediterranean (WHO EMRO) [54,55]. Our qualitative research with informants in regional organisations confirms and elaborates on the important roles played by these two WHO regional offices [45]. However, we excluded United Nations specialised technical agencies to highlight African-initiated and owned regional institutions.…”
Section: Methodssupporting
confidence: 62%
See 4 more Smart Citations
“…International organisations, like the WHO Regional Office for Africa (WHO AFRO), have well-documented involvement and influence on African health research agendas and capacity as evidenced by the ongoing studies by WHO AFRO using data from the African Barometer collected from health research focal points in country [32] or similar studies with the WHO Regional Office for the Eastern Mediterranean (WHO EMRO) [54,55]. Our qualitative research with informants in regional organisations confirms and elaborates on the important roles played by these two WHO regional offices [45]. However, we excluded United Nations specialised technical agencies to highlight African-initiated and owned regional institutions.…”
Section: Methodssupporting
confidence: 62%
“…Health, science, and higher-education decision-makers in government shared that they saw opportunities for using regional organisations to include health sciences research as a domain of cooperation (where there were not already dedicated regional bodies for this such as in Western and Eastern Africa) [24]. In a more recent qualitative study, we found that regional organisations in Africa are more involved in governance and research use and dissemination, than financing or infrastructure development-with capacity strengthening activities more focused on individual human resources than institutions [45]. Some regional organisations have policies specific to health research, such as the African Union Development Agency's Health Research and Innovation Strategy for Africa (2018-2030) [46] and the WHO's Regional Office for Africa Research for Health Strategy for the African Region (2016-2025) [47].…”
Section: Introductionmentioning
confidence: 82%
See 3 more Smart Citations